Smart Transformation of a Polyhedral Oligomeric Silsesquioxane Shell Controlled by Thiolate Silver(I) Nanocluster Core in Cluster@Clusters Dendrimers. (30th August 2018) - Li, Si; Wang, Zhao‐Yang; Gao, Guang‐Gang; Li, Bing; Luo, Peng; Kong, Yu‐Jin; Liu, Hong; Zang, Shuang‐Quan
Abstract: Using polyhedral oligomeric silsesquioxane (POSS) modified by a thiol group as a protected ligand, atom‐precise multi‐heteorocluster‐based dendrimers Ag12 @POSS6 (1 a and 1 b ) were assembled. Through the reactive −SH groups, six POSS shell ligands stabilize the central 12‐core silver(I) cluster by diverse Ag−S interactions. When such Ag12 @POSS6 complex was stimulated by different solvents (acetone or tetrahydrofuran), the core Ag12 silver(I) cluster underwent reversible structural transformation between flattened cubo‐octahedral (in 1 a ) and normal cubo‐octahedral (in 1 b ); concomitantly shell POSS clusters rearranged from pseudo‐octahedral to quasi‐octahedral. Furthermore, the film matrix modified by 1 a or 1 b showed different hydrophobicity.